Kebijakan Kepala Sekolah dalam Membentuk Karakter Siswa di SMK N 1 Paguyaman Pantai - Ahili, Sandrianto; Ngiu, Zulaecha; Lukum , Roni (Innovative: Journal Of Social Science Research, 2025)
Research to find out the principal's policy in character formation at SMK N 1 Paguyaman Pantai, Boalemo Regency. This study uses a descriptive research type with a qualitative approach. The location of this research was conducted in Bubaa Village, Paguyaman Pantai District, Boalemo Regency, with data sources obtained from several informants such as the principal, vice principal for curriculum, subject teachers and students at SMK N Paguyaman Pantai. Data collection was carried out using observation, interview and documentation methods. The researcher acted as an information digger with the aim of obtaining both primary and secondary data sources. The results of this study explain that the policy of the principal of SMK N 1 Paguyaman Pantai in forming student character has been going well. This can be seen from his role in the aspects of adjustment, process aspects and function aspects. Before entering the new school year, the principal prepares a teaching and learning implementation plan at the school together with educators and education staff, parents and the school committee. In the discussion, the principal also emphasized the importance of internalizing character education in learning. The principal also evaluates the implementation of teaching and learning in the school to find out whether the agreed plan is implemented or not. The character building strategy carried out at SMK N 1 Paguyaman Pantai, namely by prioritizing exemplary attitudes, habituating the creation of conducive conditions, and integration and internalization. All of these attitudes have been implemented well in the school environment.